Perkembangan Pentadbiran Pensijilan Halal di Malaysia 1974-2016: Satu Tinjauan - Pauzi, Norhidayah; Man, Sa'adan (Online Journal of Research in Islamic Studies, 2018)
Malaysia as known as Islamic state in the ASEAN region (Association of Southeast Asian Nations) has various strategic action plans for driving the development of Malaysia's halal certification. However, how does the history of Malaysia’s halal institution is beginning and what are the main factors that affect it? This article focuses on the history of Malaysia’s halal certification, the procedures of halal certifications and the factors affecting the growth of halal institutions in Malaysia. Research studies have used the methods of datas collection through library research (documentation method) and field studies (interview method). The findings show that the background of development of halal institutions in Malaysia was started from government’s awareness in line with a government initiative to make Malaysia as a world halal hub. Other factors are dependency by the government on imported food products and the highly demand in the food processing sector.